Panel Discussion 2 - Research data repositories: Where are we now? Where do we go next? [video] - SUBAGYO, Hendro (Institutional Knowledge at Singapore Management University, 2021)
To better support sharing of research data, many organisations have setup research data repositories and provide advocacy on research data sharing and reuse. It is now timely to reflect on the state of research data repositories and the evolution of services that data managers provide. The panellists will share their experiences in managing research data repositories and navigating through the various opportunities and challenges. They will also discuss about the future possibilities, such as growth and sustainability, of research data repositories.Moderator: Yuyun W. ISHAK, Assistant Director, Nanyang Technological University LibraryPanellists: Hendro SUBAGYO, Acting Head of Center for Scientific Data and Information, and Madiareni SULAIMAN, Research Data Librarian, National Scientific Repository, National Research and Innovation Agency, Republic of Indonesia (formerly Indonesian Institute of Science) Shuai WANG, Associate Professor, and Sae TANIGUCHI, Project Specialists, Centre for Social Research and Data Archives, Institute of Social Science, The University of Tokyo Wendy Hoi Yan WONG, Research Data Librarian, The Chinese University of Hong Kong Library Naomi WAITHIRA, Head of Data Management, Mahidol Oxford Tropical Medicine Research Unit, Mahidol University